1996
DOI: 10.1093/jac/38.5.885
|View full text |Cite
|
Sign up to set email alerts
|

Development of guidelines for gentamicin dosing

Abstract: The performance of dosage guidelines for starting gentamicin therapy was evaluated prospectively in 50 patients with suspected or proven Gram-negative septicaemia and the results were compared with results from similar group of 50 patients for whom the guidelines were not followed. Peak concentrations were significantly higher when the guidelines were followed (7.2 (+/- 1.9) mg/L vs 5.7 (+/- 1.8) mg/L) but there was no difference in trough concentrations. Fifty-eight per cent of patients had both peak and trou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Although once-daily administration of aminoglycosides has been applied widely, there has been little uniformity in the regimens for dose, dosing interval and monitoring method used [8,[20][21][22][23][24]. For the effective and safe use of the aminoglycosides it is important to achieve sufficiently high peak blood concentrations to maximize efficacy and at the same time avoid prolonged continuous exposure of high concentrations to minimize toxicity and permit the reversal of the adaptive post-exposure resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Although once-daily administration of aminoglycosides has been applied widely, there has been little uniformity in the regimens for dose, dosing interval and monitoring method used [8,[20][21][22][23][24]. For the effective and safe use of the aminoglycosides it is important to achieve sufficiently high peak blood concentrations to maximize efficacy and at the same time avoid prolonged continuous exposure of high concentrations to minimize toxicity and permit the reversal of the adaptive post-exposure resistance.…”
Section: Discussionmentioning
confidence: 99%
“…12,24,48,50 Begg et al 24 derived a table with recommended AUCs based on normal renal function, using loading doses of 5, 6, or 7 mg/ kg. Barclay et al 12 implemented this dosing method and found that the target AUC method resulted in fewer dosage changes, with more patients reaching the study's target AUC range of 72-101 mg · hr/L.…”
Section: Comparison Of Once-daily Dosing Methodsmentioning
confidence: 99%
“…In general, GENT is administered once a day in order to exploit its concentrationdependent bactericidal activity against Gram-negative bacteria. For life-threatening infections, the targeted peak and trough serum concentrations are 8 to 10 and 1 to 2 g/ml, respectively (16,17). In single-drug time-kill studies, we first used a GENT concentration of 10 g/ml.…”
mentioning
confidence: 99%